Is the Face an Air Bag for the Brain and Torso?—The Potential Protective Effects of Severe Midface Fractures. Issue 8 (August 2018) - Woriax, Hannah E.; Hamill, Mark E.; Gilbert, Carol M.; Reed, Christopher M.; Faulks, Emily R.; Love, Katie M.; Lollar, Daniel I.; Nussbaum, Michael S.; Collier, Bryan R.
We investigated the patterns of injury associated with major midface trauma. Our hypothesis is that midface injuries are associated with a decrease in certain traumatic brain injuries as well as major torso injuries. The registry of our Level I trauma center was queried for all adult patients treated over 25 years from 1989 to 2013. Patients with midface fractures were identified based on the ICD-9 code. Associated injuries were defined based both on individual ICD-9 codes as well as the Barell Injury Matrix. Injury etiology was defined based on e-codes. Univariate analysis was performed using chi-squared test, Fisher's exact test, and Wilcoxon test. A total of 29, 152 patients were identified. Excluding pediatric patients, those with exclusively penetrating trauma, and patients with incomplete data, 20, 971 patients were included for subsequent analysis. Midface fractures were identified in 752 patients. Patients with Le Fort fractures were more likely to be male, have a higher Injury Severity Score, a lower arrival Glasgow Coma Scale, and more likely to require intensive care unit admission and mechanical ventilation, with a longer hospital length of stay. Patients with midface fractures had significantly fewer subdural hematomas, subarachnoid hemorrhages, spine fractures, and were less likely to have associated abdominal and pelvic injuries. Patients with midface fractures were more likely to require facial reconstruction procedures and craniotomy. Patients presenting with midface fractures after blunt trauma have a distinctly different pattern of injuries. One potential mechanism for this is a deceleration effect, where midface impact and resulting fractures dissipate some of the energy.